Associations Between Workplace Exercise Interventions and Job Stress Reduction: A Systematic Review. (December 2019) - Park, Sungwon; Jang, Min Kyeong
Background: High job stress is positively associated with reduced quality of life in workers, detrimental effects on worker health, and increased worker absenteeism and lower productivity. Exercise is a proven approach for coping with psychological stress in general. However, relatively few research studies have examined the effects of workplace exercise interventions on job stress reduction. The purpose of this systematic review was to identify associations between workplace exercise interventions and job stress reduction among employees. Methods: A literature search was performed using five databases (i.e., CINAHL, Medline via PubMed, Scopus, PsycINFO, and Embase), and eligible studies were written in English, and were published between January 1990 and October 2018. Studies were included if worker participants were subjected to a workplace exercise intervention, and their job stress was measured before and after the intervention. To assess the quality of these studies, van Tulder's risk of bias assessment tool was applied. Findings: Eight studies were identified, and six of those (75%) were found to be of relatively good quality. In only two of the studies (25%) was the workplace exercise program associated with a statistically significant reduction in job stress. The study findings suggest that relationships between workplace exercise interventions and job stress reduction have not been sufficiently evaluated in the literature. Conclusion and Application to Practice: Based on the limited data available, future intervention research should focus on randomized controlled trials of interventions incorporating both exercise and multidimensional strategies to reduce job stress.